2023
DOI: 10.1021/acs.chemmater.3c01227
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Aldehyde-Functional Diblock Copolymer Spheres onto Surface-Grafted Polymer Brushes via Dynamic Covalent Chemistry Enables Friction Modification

Abstract: Dynamic covalent chemistry has been exploited to prepare numerous examples of adaptable polymeric materials that exhibit unique properties. Herein, the chemical adsorption of aldehyde-functional diblock copolymer spherical nanoparticles onto amine-functionalized surface-grafted polymer brushes via dynamic Schiff base chemistry is demonstrated. Initially, a series of cis-diol-functional sterically-stabilized spheres of 30–250 nm diameter were prepared via reversible addition–fragmentation chain transfer (RAFT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 93 publications
1
16
0
Order By: Relevance
“…If nanoparticle adsorption is desired, then an attractive interaction force between the brush and the nanoparticles must be introduced to overcome the repulsive force. Recently, we exploited dynamic covalent chemistry (more specifically, imine bond formation) to adsorb aldehyde-functional nanoparticles onto amine-functional polymer brushes . Herein we examine whether the formation of acetal bonds between cis -diol-functional PGMA 51 –PBzMA y nanoparticles and a hydrophilic aldehyde-functional polymer brush is sufficient to promote adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If nanoparticle adsorption is desired, then an attractive interaction force between the brush and the nanoparticles must be introduced to overcome the repulsive force. Recently, we exploited dynamic covalent chemistry (more specifically, imine bond formation) to adsorb aldehyde-functional nanoparticles onto amine-functional polymer brushes . Herein we examine whether the formation of acetal bonds between cis -diol-functional PGMA 51 –PBzMA y nanoparticles and a hydrophilic aldehyde-functional polymer brush is sufficient to promote adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we exploited dynamic covalent chemistry (more specifically, imine bond formation) to adsorb aldehyde-functional nanoparticles onto amine-functional polymer brushes. 59 Herein we examine whether the formation of acetal bonds between cis -diol-functional PGMA 51 –PBzMA y nanoparticles and a hydrophilic aldehyde-functional polymer brush is sufficient to promote adsorption. It is well-known that acetal bond formation is (i) acid-catalyzed and (ii) more entropically favorable when using a diol rather than two separate alcohols.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These surface layers have been shown to have many desirable properties [ 36 ], including increased antifouling [ 36 ] and lubricity [ 37 ] and can act as a scaffold for various small and large molecules [ 38 ], [ 39 ]. In the example presented here, a hydrophilic aldehyde functional polymer brush (PAGEO5MA) was grown from a glass cover slip [ 40 ], [ 41 ], [ 42 ], with a dry thickness = 40 nm, before decoration with an amino-functionalised Nile Red analogue (2-(2-Aminoethoxy) Nile Red) [ 43 ]. We have shown that PAGEO5MA can be conjugated with reactive amines through reductive amination chemistry to produce highly functionalised coatings ( 80 % of available reactive sites) [ 40 ], [ 41 ], [ 42 ].…”
Section: Worked Examplesmentioning
confidence: 99%